Zur sprachlichen Ungleichbehandlung von Frauen und Männern im System der deutschen Personenbezeichnungen - Błaszkowska, Hanka (Studia Germanica Posnaniensia, 2018)
The subject of the author's considerations is the women's discrimination in the German system of personal nouns and pronouns, viewed from the feminist linguistics standpoint. The women's dependence on men is expressed among others by the domination of masculine gender in surnames, titles and names of profession. The respective morphological and referential asymmetry is looked upon as a kind of social disregard. It also applies to the pronominal system, especially to the forms of indefinite pronouns. Two "therapeutic" measures have been proposed: feminization, i.e. obligatory feminine marking, and neutralization, i.e. unisex denotations.